Pengaruh Pelayanan Online oleh Disdukcapil Terhadap Kepuasan Masyarakat Kota Cimahi - Pasya, Mochammad Kemal Maulana; Soesilo, Soesilo; Suryaman, Warman (Universitas Batanghari Jambi, 2024)
Public services, especially the quality or level of service provided by government employees to the community, is often one of the problems that often arise in public relations with local governments. Service standards that must be offered by the government as a provider of public goods and services have increased. The Cimahi City Population and Civil Registry Office is a local government organization that has the responsibility of making residence documents for various kinds of goods needed by the community. The research objective is to find out the effect of online services by Disdukcapil on community satisfaction. The method used is quantitative with a total of 31 respondents. The analysis technique used statistical analysis through regression, correlation, determination, and hypothesis testing. The results show that online services (X) have a simultaneous effect on community satisfaction (Y). The remaining 14.3% is influenced by other factors that are not present in this study. This shows that the better the online services provided by officials at the Population and Civil Registration Service, the more people's satisfaction will increase.